Teacher Shocks and Student Learning : Evidence from Zambia. - Das, Jishnu; Dercon, Stefan; Habyarimana, James; Krishnan, Pramila (World Bank, Washington, DC, 2012)
A large literature examines the link between shocks to households and the educational attainment of children. The authors use new data to estimate the impact of shocks to teachers on student learning in mathematics and English. Using absenteeism in the 30 days preceding the survey as a measure of these shocks they find large impacts: A 5 percent increase in the teacher's absence rate reduces learning by 4 to 8 percent of average gains over the year. This reduction in learning achievement likely reflects both the direct effect of increased absenteeism and the indirect effects of less lesson preparation and lower teaching quality when in class. The authors document that health problems-primarily teachers' own illness and the illnesses of their family members-account for more than 60 percent of teacher absences; not surprising in a country struggling with an HIV/AIDS epidemic. The relationship between shocks to teachers and student learning suggests that households are unable to substitute adequately for teaching inputs. Excess teaching capacity that allows for the greater use of substitute teachers could lead to larger gains in student learning.